Spatial Characterization of Channeling in Sheared Rough‐Walled Fractures in the Transition to Nonlinear Fluid Flow - Robert Egert; Fabian Nitschke; Maziar Gholami Korzani; Thomas Kohl (Water Resources Research, 2023)
Abstract Accurate quantification of spatially resolved fluid flow within fractures is crucial for successful reservoir development, such as Enhanced Geothermal Systems. This study presents an innovative workflow designed to model and characterize preferential flow paths (channels) within rough‐walled shear fractures. A set of 30 rough‐walled self‐affine fractures, all possessing identical roughness characteristics, is stochastically generated. By solving the nonlinear Navier‐Stokes equations in 420 individual realizations, the transition from linear to nonlinear flow regimes and the two extreme flow directions perpendicular and parallel to the shearing are numerically captured. A distinguishing feature of this approach is its comprehensive statistical analysis, which encompasses both the geometric and transport properties of flow paths in the non‐simplified three‐dimensional fractured void space under typical geothermal flow conditions. In a perpendicular orientation of flow and shearing, fluid flow exhibits pronounced localization, with more than one‐third of the volumetric flow concentrated within 15% of the fracture volume. In contrast, parallel to the shearing, a complex pattern of individual tortuous channels emerges, with flow occurring in 22% of the void space. Nonlinear effects primarily manifest outside these channels, suggesting that complex flow phenomena may dominate irregular fracture structures, such as contact zones or asperities. In the parallel case, increased flow rates lead to an amplification of channeling processes resulting in less affected volume and diminished tortuosity of the main flow path, while in perpendicular orientation nonlinear effects are only of minor importance. The small‐scale flow regime of both extreme cases tends to converge with increasing flow rates.